Leadership roles and management functions in nursing : theory and application - Marquis, Bessie L.; Huston, Carol Jorgensen (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Includes many exercises along with discussions of theory that teach nursing students how to integrate effective management skills with leadership skills. This book helps students develop the critical thinking ability needed to apply skills on the job - from organizing patient care to motivating staff to managing conflict